Retraction Note: Health-related quality of life among ethnic minority residents in remote Western China: a cross-sectional study - Jiaxin Dong; Xiaoju Li; Rong Fan; Jielin Yang (BMC Public Health, 2023)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s12889-023-16559-x.